ANALISIS PENGAKUAN PENDAPATAN DAN BEBAN PADA PT. ASURANSI ADIRA DINAMIKA CABANG MANADO - Iroth, Natasia; Sondakh, Jullie J.; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2020)
Concerning about the public interests and companies interests for financing which can be done by transferring loans to insurance companies. Every company needs to apply applicable accounting standards. Financial approval in accordance with the required standards is very important.Â The purpose of this study was to determine whether income and expenses at PT. Asuransi Adira Branch of Manado complies with statement of financial accounting standard number 28. The analytical method used is descriptive, to analyze the suitability between the recognition of income and expenses made by the company with applicable standards. The results showed that PT. Asuransi Adira Branch of Manado should continue to strive to continue making statement of financial accounting standard number 28 as a guideline in accounting practices.